A low-dissipative solver for turbulent compressible flows on unstructured meshes, with OpenFOAM implementation. (18th July 2017) - Modesti, Davide; Pirozzoli, Sergio
Highlights: Kinetic energy conservation in finite volume schemes. Compressible low-dissipative solver exploiting AUSM dissipative fluxes. Implementation in OpenFOAM library. Abstract: We develop a high-fidelity numerical solver for the compressible Navier–Stokes equations, with the main aim of highlighting the predictive capabilities of low-diffusive numerics for flows in complex geometries. The space discretization of the convective terms in the Navier–Stokes equations relies on a robust energy-preserving numerical flux, and numerical diffusion inherited from the AUSM scheme is added limited to the vicinity of shock waves, or wherever spurious numerical oscillations are sensed. The solver is capable of conserving the total kinetic energy in the inviscid limit, and it bears sensibly less numerical diffusion than typical industrial solvers, with incurred greater predictive power, as demonstrated through a series of test cases including DNS, LES and URANS of turbulent flows. Simplicity of implementation in existing popular solvers such as OpenFOAM is also highlighted.